Feminist Collections, v.13, no.3 (spring 1992) - (:unkn) unknown (My University, 1992)
Subtitle: A Quarterly of Women's Studies Resources. 34p.
BOOK REVIEWS: FEMINISM AND ITS DISCONTENTS, by Lisa D. Brush.[Reviews of] Feminist Fatale: Voices from the "Twentsomething" Generation Explore the Future of the "Women's Movement," by Paula Kamen; Surviving the Blues: Growing Up in the Thatcher Decade, ed. by Joan Scanlon; More Joy Than Rage: Crossing Generations with the New Feminism, by Cary1 Rivers. CARING AND WOMEN'S LIVES, by Carolyn Keith.[Reviews of] Circles of Care: Work and Identity in Women's Lives, ed. by Emily K. Abel and Margaret K. Nelson; Prisoners of Men's Dreams: Striking Out for a New Feminine Future, by Suzanne Gordon; Counting on Kindness: The Dilemmas of Dependency, by Wendy Lustbader. FEMINISTS DISCUSS THEIR PERSPECTIVES OF LEGAL THEORIES, by Teresa (Tess) Meuer.[Reviews of] At the Boundaries of Law: Feminism and Legal Theory, ed. by Martha Albertson Fineman and Nancy Sweet Thomadsen; Feminist Legal Theory: Readings in Law and Gender, ed. by Katharine T. Bartlett and Rosanne Kennedy. THE JUNE L. MAZER LESBIAN COLLECTION: By Claudia A. Brink. FINDING WOMEN IN GOVERNMENT DOCUMENTS: CD-ROM PRODUCT HELPS: By Robin Paynter. COMPUTER TALK. WISCONSIN BIBLIOGRAPHIES IN WOMEN'S STUDIES. RESEARCH EXCHANGE. NEW REFERENCE WORKS IN WOMEN'S STUDIES: Two works on the abortion debate; two on film history and criticism; two sourcebooks on international women; a biographical dictionary of women in classical mythology; a bibliography on feminist spirituality; a resource on sex in mass media and its effect on adolescents; a guide to research on American Indian women; a bibliography of war and peace in North American women's fiction; a guide to women's history in periodical literature; a bibliography on Shakespeare; and a bibliography on the feminist movement. (Reviewed by Phyllis Holman Weisbard) PERIODICAL NOTES: New periodicals on campus women; Asian women; women in world markets and home working; Thai women; gay and lesbian Mormons; gay and lesbian Christians; the World Bank's development projects for women; health issues; and Yiddish women's literature. Special issues of periodicals on women's issues as presented at the Fall 1991 UW System Women's Studies Conference; women scientists; divorce; Middle Eastern women; feminist film criticism; paid employment; Ursula K. Le Guin. Transitions: Death of the editor of Bitch, women's rock magazine, leaves the magazine in limbo. Anniversary issues from Calyx and Psychology of Women Quarterly. (Compiled by Linda Shult) ITEMS OF NOTE: A pamphlet on Arab women; a report on Latin American women, poverty, and the environment; a clearinghouse on legal issues for battered women; a series of "interactive" essays; an informational brochure on domestic violence; statistics on the rape alcohol connection; a report on sexual harassment research and resources; papers aimed at improving campus climate for Black women and Hispanic women; a summary report on education equity and gender bias; photographs of women in mathematics and science; a board game on women in politics; a poster on awareness of sexist language; a catalog summarizing research on two hundred social and behavioral science studies; a bibliography on women adult educators; a catalog of books related to Women's History Month; and a mail-order service for feminist books. (Compiled by Ingrid Markhardt) BOOKS RECENTLY RECEIVED.
Keywords: Women's Studies; Gender; Feminism; Library Resources; Reviews